Hyaluronic acid decorated pH- and temperature-induced injectable bioconjugates for sustained delivery of bioactive factors and highly efficient wound regeneration. (27th November 2019) - Thambi, Thavasyappan; Giang Phan, V. H.; Kim, Seong Han; Duy Le, Thai Minh; Lee, Doo Sung
Abstract : Microporous injectable biogels, composed of hyaluronic acid-poly(β-amino urethane) bioconjugates, which can seal cutaneous wounds and deliver bioactive factors for tissue regeneration have been developed. Abstract : Microporous injectable bioconjugates, composed of hyaluronic acid–poly(β-aminoester urethane), were prepared by the amination of synthetic copolymers and successive post modification using natural polymers. Strinkingly, the free flowing bioconjugates can seal cutaneous wounds due to their sharp sol-to-gel phase transition. The sustained delivery of bioactive factors and wound regeneration performance of the bioconjugates were examined in vivo .